Decay of the Solutions of Parabolic Equations with Double Nonlinearity and the Degenerate Absorption Potential - Stepanova, E. V. (Ukrains’kyi Matematychnyi Zhurnal, 2014)
We study the behavior of solutions for the parabolic equation of nonstationary diffusion with double nonlinearity and a degenerate absorption term: (| u|^q-1 u)_t-_i=1^Nx_i(| abla_x u|^q-1ux_i)+a_0(x)| u|^λ -1 u=0, where \( a_0(x)d_0 (-ω (| x|)| x|^q+1 ) \) , d 0 = const > 0, 0 ≤ λ 0 for τ > 0, and \( _0+ω (τ )τ dτ